Pengaruh Budaya Organisasi Dan Komunikasi Interpersonal Terhadap Kualitas Pelayanan Administrasi Kependudukan Di Kelurahan Medan Satria Bekasi - Muthia Novita Ramadhani; Tungga Buana Irfana; Supriyanto Supriyanto; Djuni Thamrin; Matdio Siahaan (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
The purpose of this study was to determine the effect of organizational culture and interpersonal communication on the quality of population administration services in Medan Satria Village, Bekasi. The type of research used in this research is quantitative research. The sampling technique used in this study was Probability Sampling with Random Sampling, namely 76 respondents. The data processing tool used in this research is using SPSS version 27. Based on the results of the study, it shows that partially the organizational culture variable has a positive effect on the quality of population administration services which shows a value of 3.633 t-count> 1.993 t-table with a significance value of 0.001 <0.05. In addition, the interpersonal communication variable partially has a positive effect on the quality of population administration services which shows a value of 5,367 t-count> 1,993 t-table with a significance value of 0.000 <0.05. and based on the simultaneous results obtained from this study, the organizational culture and interpersonal communication variables have a positive effect on the quality of population administration services by obtaining a value of 56,123 f-count> 3.12 f-table.